Study on Maximum Power Point Tracking Algorithm of Automobile Exhaust Thermoelectric Generator - Quan, Rui (Applied Mechanics and Materials, 2014)
Considering the soft output performance of automobile exhaust thermoelectric generator (AETEG), an AETEG using Buck based DC/DC converter were established, based on the duty ratio disturbance observation method, an improved maximum power point tracking algorithm (MPPT) named adaptive hill climbing algorithm was present, including its principle and flow diagram. The simulation result based on UDDS driving cycle proves that the practical power of AETEG can follow its theoretic maximum output power, the algorithm has advantages on the dynamic and steady performance of AETEG in the MPPT.